Cost-Effective, Disposable, Flexible, and Printable MWCNT-Based Wearable Sensor for Human Body Temperature Monitoring - K., Thiyagarajan; Rajini, G. K.; Maji, Debashis (IEEE sensors journal, 2022)
Personalized mobile healthcare integrated with various wearable devices has become a significant area of interest in the present era. In the current research work, a flexible, wearable and disposable paper-based continuous skin temperature monitoring sensor for early medical prognosis and accurate diagnosis of body temperature-related ailments, such as COVID-19, is proposed. Conventional screen-printing and drop-casting techniques were used to fabricate the proposed sensor using MWCNTs as the sensing material and paper as the substrate. The linearity, stability, repeatability and durability of the sensors were tested from 29°C (room temperature) to 60°C. A thin sheet of PET was laminated over the sensor surface to ascertain its stability toward environmental effects and physical movements, and a response time of ~13 s and a recovery time of ~38 s with a sensitivity of −0.0685% °C −1 were recorded. The efficacy of the proposed sensor was ascertained by placing it at different body locations on a human subject and comparing it with a standard thermocouple and IR sensor. The sensor even helped to effectively distinguish minimal temperature variations between various regions of the body. Furthermore, the feasibility of the fabricated temperature sensor as a temperature-based tactile sensor for robotics/artificial skin applications and as a noncontact breath monitoring device for use in personalized healthcare monitoring applications was investigated.